2017
DOI: 10.1007/s00246-017-1648-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 6-mm Versus 8-mm-Tip Cryoablation Catheter for the Treatment of Atrioventricular Nodal Reentrant Tachycardia in Children: A Prospective Study

Abstract: Due to its safety profile, cryoablation (Cryo) for atrioventricular nodal reentrant tachycardia (AVNRT) is more commonly preferred over radiofrequency (RF) ablation in children in recent years. Recent studies demonstrated high long-term success rates comparable to radiofrequency ablation. The aim of this prospective study was to compare the efficacy and safety of an 8-mm-tip versus 6-mm-tip Cryo catheter in the treatment of AVNRT in children. A total of 125 consecutive patients over 10 years of age with AVNRT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Ensite NavX system can be used for accurate navigation. The advantages of three dimensional mapping system has been widely discussed in previous studies [8,12,[25][26][27][28][29]. According to our experience, the guidewires Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Ensite NavX system can be used for accurate navigation. The advantages of three dimensional mapping system has been widely discussed in previous studies [8,12,[25][26][27][28][29]. According to our experience, the guidewires Fig.…”
Section: Discussionmentioning
confidence: 78%
“…Consequently, our final analysis included 27 studies 7–9,16–39 (7 randomized studies and 20 observational studies analyzing 5110 patients who have AVNRT indicated for ablation. Cryoablations were performed 25 studies which categorized into 10 studies with 4‐mm tip catheter, 12 studies with 6‐mm tip catheter, and 3 studies with 8‐mm tip catheter.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 27 studies 7–9,16–39 with retrievable information were considered for analysis. We conducted a descriptive assessment to evaluate the acute procedural success rate for each technique.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations